Influence of Gamma Radiation on Some Optical Properties and Urbach Energy of (PMMA- Doped Red Methyl) Films - Wadi, Hala Abd Alsahib (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
We have studied the effect of gamma irradiation on the optical transmission, absorbance, absorption coefficient,  and Urbach energy for (PMMA- doped red methyl) film deposited by using solvent casting method .The optical transmission (T %) in the wavelength range (1901100 ) nm of films was measured , it was seen that all the parameters were affected by gamma irradiation.